Selection by genetic merit in Cavia porcellus for reproduction by their selection index - Saucedo U., José (2018)
The study was carried out in the "Centro de Producción de Genética Superior (CENPROGEN-SUP)" in Valle de Condebamba district, Cajamarca region, Peru, with the objective of selecting male guinea pigs for breeding based on their selection index. A total of 80 male guinea pigs of the Cajamarca ecotype of the Facultad de Ingeniería en Ciencias Pecuarias (pure and crossbred FICP) of the National University of Cajamarca, as well from the Valley of Mangallana and from the Valley of Cholocal. The guinea pigs were fed alfalfa, concentrate and water ad libitum for 56 days. The daily weight gain (IPD) and total weight gain (IPT), final weight (PF), body length (LC) and feed conversion (CA) were evaluated. The crossed FICP had significantly better values for IPD, IPT, PF and LC (17.6±1.8 g, 979±98 g, 1328±134 g and 36.6 ± 1.3 cm, respectively) (p<0.05).) On the other hand, there were no differences between groups for feed conversion. A high and significant correlation was found (p<0.05) between PF with LC and feed intake, and inverse correlation (p<0.05) between IPT and CA. The maximum value of the selection index corresponds to crossbred FICP guinea pigs (0.873), followed by pure FICP (0.544), Valley of Mangallana (0.400) and Valley of Cholocal (0.346), and 45% of the first quartile corresponds to crossbred FICP. Best germplasm with genetic superiority was found in the crossbred FICP population.